Polymorphisms of the cryptochrome 2 and mitoguardin 2 genes are associated with the variation of lipid-related traits in Duroc pigs - Emilio Mármol-Sánchez (Nature Portfolio, 2019)
Abstract The genetic factors determining the phenotypic variation of porcine fatness phenotypes are still largely unknown. We investigated whether the polymorphism of eight genes (MIGA2, CRY2, NPAS2, CIART, ARNTL2, PER1, PER2 and PCK1), which display differential expression in the skeletal muscle of fasted and fed sows, is associated with the variation of lipid and mRNA expression phenotypes in Duroc pigs. The performance of an association analysis with the GEMMA software demonstrated that the rs330779504 SNP in the MIGA2 gene is associated with LDL concentration at 190 days (LDL2, corrected P-value = 0.057). Moreover, the rs320439526 SNP of the CRY2 gene displayed a significant association with stearic acid content in the longissimus dorsi muscle (LD C18:0, corrected P-value = 0.015). Both SNPs were also associated with the mRNA levels of the corresponding genes in the gluteus medius skeletal muscle. From a biological perspective these results are meaningful because MIGA2 protein plays an essential role in mitochondrial fusion, a process tightly connected with the energy status of the cell, while CRY2 is a fundamental component of the circadian clock. However, inclusion of these two SNPs in chromosome-wide association analyses demonstrated that they are not located at the peaks of significance for the two traits under study (LDL2 for rs330779504 and LD C18:0 for rs320439526), thus implying that these two SNPs do not have causal effects.